ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOID EKSTRAK ETANOL PANDAN HUTAN JENIS BARU FREYCINETIA SESSILIFLORA RIZKI - Fitri Sri Rizki; Ade Ferdinand (Jurnal Insan Farmasi Indonesia, 2021)
West Kalimantan is a tropical area whose territory consists of swampy areas, highlands, lowlands, and mountains which have the potential to be a place to live for medicinal plants. One of the new types of forest pandanus plant, Freycinetia sessiliflora Rizki, found on Mount Passi, Singkawang, has not been widely exposed to scientific knowledge. This study aims to isolate the flavonoid compounds contained in pandan ethanol extract by maceration extraction using 96% ethanol. Identification of flavonoid compounds was carried out by wiltrater, 10% NaOH, and H2SO4 (concentrated) tests. Isolation of flavonoids by Thin Layer Chromatography and Column Chromatography. The results of several tests showed that there were flavonoids contained in the ethanol extract pandanus Freycinetia sessiliflora Rizki.